Islam and nation : separatist rebellion in Aceh, Indonesia - Aspinall, Edward (Singapore : NUS Press, 2009)
'Rooted in the latest theoretical debates about nationalism and ethnicity, yet written in an accessible and engaging style, Islam and Nation presents a fascinating study of the genesis, growth and decline of a nationalist movement. Drawingon hundreds of interviews with nationalist leaders, activists and guerillas, Aspinall reveals how the Free Aceh Movement went from being a quixotic fantasy to a guerilla army in the space of a generation, leading to a bitter conflict in which thousands perished. And by exploring the complex relationship between Islam and nationalism, Aspinall also explains how a society famed for its Islamic piety gave rise to a guerilla movement that ended up rejecting the Islamic goals of its forebears. Islam and Nation is a tour de force in the study of nationalist politics. It will be of great interest to readers concerned about Southeast Asia, Islamic politics, ethnic conflict and nationalism everywhere.' -- Back cover
Includes bibliographical references (p. [265]-275) and index.
Keywords: Gerakan Aceh Merdeka -- History; Nationalism -- Indonesia -- Nanggroe Aceh Darussalam -- History; Nationalism -- Religious aspects -- Islam; Islam and politics -- Indonesia -- Nanggroe Aceh Darussalam; Nanggroe Aceh Darussalam (Indonesia) -- History -- Autonomy and independence movements; Nanggroe Aceh Darussalam (Indonesia) -- Politics and government